# Logarithmic Proof (23/03/2015)

Prove that: $\ln { \left( xy \right) } =\ln { x+\ln { y } }$

Now, say that: ${ a }^{ m }=x\\ \\ \therefore \quad \log _{ a }{ x=m } \\ \\ { a }^{ q }=y\\ \\ \therefore \quad \log _{ a }{ y } =q$

So… $LHS\\ \\ =\ln { \left( { a }^{ m }\cdot { a }^{ q } \right) } \\ \\ =\ln { \left( { a }^{ \left( m+q \right) } \right) } \\ \\ =\left( m+q \right) \cdot \ln { a } \\ \\ =\left( \log _{ a }{ x } +\log _{ a }{ y } \right) \cdot \log _{ e }{ a } \\ \\ =\frac { \log _{ a }{ x } +\log _{ a }{ y } }{ \log _{ a }{ e } } \\ \\ =\frac { \log _{ a }{ x } }{ \log _{ a }{ e } } +\frac { \log _{ a }{ y } }{ \log _{ a }{ e } } \\ \\ =\log _{ e }{ x } +\log _{ e }{ y } \\ \\ =\ln { x } +\ln { y } \\ \\ =RHS$

# Experiments With Surds & Exponentials… $\sqrt { a } \sqrt { a } ={ a }^{ \frac { 1 }{ 2 } }{ a }^{ \frac { 1 }{ 2 } }={ a }^{ \frac { 1 }{ 2 } +\frac { 1 }{ 2 } }=a\\ \\ \sqrt [ 3 ]{ a } \sqrt [ 3 ]{ a } \sqrt [ 3 ]{ a } ={ a }^{ \frac { 1 }{ 3 } }{ a }^{ \frac { 1 }{ 3 } }{ a }^{ \frac { 1 }{ 3 } }={ a }^{ \frac { 1 }{ 3 } +\frac { 1 }{ 3 } +\frac { 1 }{ 3 } }=a\\ \\ \sqrt [ 4 ]{ a } \sqrt [ 4 ]{ a } \sqrt [ 4 ]{ a } \sqrt [ 4 ]{ a } ={ a }^{ \frac { 1 }{ 4 } }{ a }^{ \frac { 1 }{ 4 } }{ a }^{ \frac { 1 }{ 4 } }{ a }^{ \frac { 1 }{ 4 } }={ a }^{ \frac { 1 }{ 4 } +\frac { 1 }{ 4 } +\frac { 1 }{ 4 } +\frac { 1 }{ 4 } }=a$ $\sqrt { \frac { a }{ b } } \sqrt { \frac { a }{ b } } ={ \left( \frac { a }{ b } \right) }^{ \frac { 1 }{ 2 } }{ \left( \frac { a }{ b } \right) }^{ \frac { 1 }{ 2 } }={ \left( \frac { a }{ b } \right) }^{ \frac { 1 }{ 2 } +\frac { 1 }{ 2 } }=\frac { a }{ b } \\ \\ \sqrt [ 3 ]{ \frac { a }{ b } } \sqrt [ 3 ]{ \frac { a }{ b } } \sqrt [ 3 ]{ \frac { a }{ b } } ={ \left( \frac { a }{ b } \right) }^{ \frac { 1 }{ 3 } }{ \left( \frac { a }{ b } \right) }^{ \frac { 1 }{ 3 } }{ \left( \frac { a }{ b } \right) }^{ \frac { 1 }{ 3 } }={ \left( \frac { a }{ b } \right) }^{ \frac { 1 }{ 3 } +\frac { 1 }{ 3 } +\frac { 1 }{ 3 } }=\frac { a }{ b }$ ${ a }^{ \frac { 1 }{ 2 } }=b\\ \\ \therefore \quad a={ b }^{ 2 }\\ \\ { a }^{ \frac { 3 }{ 4 } }=b\\ \\ \therefore \quad a={ b }^{ \frac { 4 }{ 3 } }\\ \\ { a }^{ \sqrt { m } }=b\\ \\ \therefore \quad a={ b }^{ \frac { 1 }{ \sqrt { m } } }\\ \\ \therefore \quad a={ b }^{ \frac { \sqrt { m } }{ m } }\\ \\ { a }^{ \frac { 1 }{ m+\sqrt { n } } }=b\\ \\ \therefore \quad a={ b }^{ m+\sqrt { n } }$

# Surd Problem…

Simplify: $\sqrt { 1 } \sqrt { 2 } \sqrt { 3 } \sqrt { 4 } \sqrt { 5 } \sqrt { 6 } \sqrt { 7 } \sqrt { 8 } \sqrt { 9 } \sqrt { 10 }$

———- $\sqrt { 1 } \sqrt { 2 } \sqrt { 3 } \sqrt { 4 } \sqrt { 5 } \sqrt { 6 } \sqrt { 7 } \sqrt { 8 } \sqrt { 9 } \sqrt { 10 } \\ \\ =\sqrt { 1 } \sqrt { 4 } \sqrt { 9 } \sqrt { 2 } \sqrt { 3 } \sqrt { 5 } \sqrt { 6 } \sqrt { 7 } \sqrt { 8 } \sqrt { 10 } \\ \\ =1\cdot 2\cdot 3\sqrt { 2 } \sqrt { 3 } \sqrt { 5 } \sqrt { 6 } \sqrt { 7 } \sqrt { 8 } \sqrt { 10 } \\ \\ =6\sqrt { 2 } \sqrt { 3 } \sqrt { 5 } \left( \sqrt { 2 } \sqrt { 3 } \right) \sqrt { 7 } \left( \sqrt { 2 } \sqrt { 2 } \sqrt { 2 } \right) \left( \sqrt { 2 } \sqrt { 5 } \right) \\ \\ =6\sqrt { 2 } \sqrt { 2 } \sqrt { 2 } \sqrt { 2 } \sqrt { 2 } \sqrt { 2 } \sqrt { 3 } \sqrt { 3 } \sqrt { 5 } \sqrt { 5 } \sqrt { 7 } \\ \\ =6\cdot 2\cdot 2\cdot 2\cdot 3\cdot 5\sqrt { 7 } \\ \\ =720\sqrt { 7 }$

# New Logarithmic Proof – Quicker Version

Prove that: $\log _{ a }{ x } =\frac { \log _{ b }{ x } }{ \log _{ b }{ a } }$

————-

PROOF: $RHS\\ \\ =\frac { \log _{ b }{ x } }{ \log _{ b }{ a } } \\ \\ =\log _{ b }{ x } \cdot \log _{ a }{ b } \\ \\ =\log _{ a }{ \left( { b }^{ \log _{ b }{ x } } \right) } \\ \\ =\log _{ a }{ x } \\ \\ =LHS$

# More Trig Shortcuts

Shortcut 1: $\cot { x } =\frac { 1 }{ \tan { x } } \\ \\ \frac { \tan { x } }{ \cot { x } } \cdot \cot { x } =\frac { 1 }{ \tan { x } } \cdot \frac { \tan { x } }{ \cot { x } } \\ \\ \tan { x } =\frac { 1 }{ \cot { x } }$

Shortcut 2: $\cot { x } =\frac { \cos { x } }{ \sin { x } } \\ \\ \frac { \sin { x } }{ \cos { x } \cot { x } } \cdot \cot { x } =\frac { \cos { x } }{ \sin { x } } \cdot \frac { \sin { x } }{ \cos { x } \cot { x } } \\ \\ \frac { \sin { x } }{ \cos { x } } =\frac { 1 }{ \cot { x } }$

Shortcut 3: $\sec { x } =\frac { 1 }{ \cos { x } } \\ \\ \frac { \cos { x } }{ \sec { x } } \cdot \sec { x } =\frac { 1 }{ \cos { x } } \cdot \frac { \cos { x } }{ \sec { x } } \\ \\ \cos { x } =\frac { 1 }{ \sec { x } }$

Shortcut 4: $\csc { x } =\frac { 1 }{ \sin { x } } \\ \\ \frac { \sin { x } }{ \csc { x } } \cdot \csc { x } =\frac { 1 }{ \sin { x } } \cdot \frac { \sin { x } }{ \csc { x } } \\ \\ \sin { x } =\frac { 1 }{ \csc { x } }$

# Sine Rule Derivation In Record Time… $\frac { 1 }{ 2 } bc\sin { A } =\frac { 1 }{ 2 } ac\sin { B } \\ \\ \frac { 2 }{ c\sin { A\sin { B } } } \cdot \frac { 1 }{ 2 } bc\sin { A } =\frac { 2 }{ c\sin { A\sin { B } } } \cdot \frac { 1 }{ 2 } ac\sin { B } \\ \\ \frac { 2bc\sin { A } }{ 2c\sin { A\sin { B } } } =\frac { 2ac\sin { B } }{ 2c\sin { A\sin { B } } } \\ \\ \frac { 2 }{ 2 } \cdot \frac { c }{ c } \cdot \frac { \sin { A } }{ \sin { A } } \cdot \frac { b }{ \sin { B } } =\frac { 2 }{ 2 } \cdot \frac { c }{ c } \cdot \frac { \sin { B } }{ \sin { B } } \cdot \frac { a }{ \sin { A } } \\ \\ \frac { b }{ \sin { B } } =\frac { a }{ \sin { A } }$

Now: $\sin { C } =\sin { \left( 90-B+\left( 90-A \right) \right) } \\ \\ \sin { C } =\sin { \left( 180-\left( A+B \right) \right) } \\ \\ \sin { C } =\sin { 180 } \cos { \left( A+B \right) -\cos { 180 } } \sin { \left( A+B \right) } \\ \\ \sin { C } =-\left( -1 \right) \sin { \left( A+B \right) } \\ \\ \sin { C= } \sin { \left( A+B \right) } \\ \\ \sin { C } =\sin { A } \cos { B } +\cos { A } \sin { B } \\ \\ \sin { C= } \frac { 2A }{ bc } \cdot \frac { x }{ a } +\frac { \left( c-x \right) }{ b } \cdot \frac { 2A }{ ac } \\ \\ \sin { C } =\frac { 2Ax }{ acb } +\frac { 2A\left( c-x \right) }{ acb }$ $\\ \\ \sin { C } =\frac { 2Ax+2A\left( c-x \right) }{ acb } \\ \\ \sin { C } =\frac { 2A\left\{ x+\left( c-x \right) \right\} }{ acb } \\ \\ \sin { C= } \frac { 2Ac }{ acb } \\ \\ \frac { ab }{ 2 } \cdot \sin { C } =\frac { 2A }{ ab } \cdot \frac { ab }{ 2 } \\ \\ \frac { 1 }{ 2 } ab\sin { C } =A\\ \\ \therefore \quad \frac { 1 }{ 2 } ab\sin { C } =\frac { 1 }{ 2 } bc\sin { A } \\ \\ \frac { 2 }{ b\sin { A\sin { C } } } \cdot \frac { 1 }{ 2 } ab\sin { C } =\frac { 2 }{ b\sin { A\sin { C } } } \cdot \frac { 1 }{ 2 } bc\sin { A } \\ \\ \frac { a }{ \sin { A } } =\frac { c }{ \sin { C } } \\ \\ \therefore \quad \frac { a }{ \sin { A } } =\frac { b }{ \sin { B } } =\frac { c }{ \sin { C } }$

# Logarithmic Differentiation As Seen In Video…

In this video, Patrick JMT demonstrated how to do logarithmic differentiation.

Now I’m going to show you how I’d solve the same problem…

Firstly we must know that: $y=x\ln { \left( \ln { x } \right) } =u\cdot v\\ \\ If\quad y=u\cdot v,\\ \\ \frac { dy }{ dx } =u\frac { dv }{ dx } +v\frac { du }{ dx } \\ \\ y=x\ln { \left( \ln { x } \right) } =u\cdot v\\ \\ u=x,\quad \frac { du }{ dx } =1\\ \\ v=\ln { \left( \ln { x } \right) } =\ln { q } \\ \\ \frac { dv }{ dq } =\frac { 1 }{ q } =\frac { 1 }{ \ln { x } } \\ \\ q=\ln { x } ,\quad \frac { dq }{ dx } =\frac { 1 }{ x } \\ \\ \therefore \quad \frac { dv }{ dx } =\frac { 1 }{ x\ln { x } } \\ \\ \therefore \quad \frac { dy }{ dx } =x\cdot \frac { 1 }{ x\ln { x } } +\ln { \left( \ln { x } \right) } \\ \\ =\frac { 1 }{ \ln { x } } +\ln { \left( \ln { x } \right) }$

Now: $y={ \left( \ln { x } \right) }^{ x }\\ \\ \ln { y=\ln { \left( { \left( \ln { x } \right) }^{ x } \right) } } \\ \\ \ln { y } =x\ln { \left( \ln { x } \right) } \\ \\ \frac { 1 }{ y } \cdot \frac { dy }{ dx } =\frac { 1 }{ \ln { x } } +\ln { \left( \ln { x } \right) } \\ \\ y\cdot \frac { 1 }{ y } \cdot \frac { dy }{ dx } =y\left\{ \frac { 1 }{ \ln { x } } +\ln { \left( \ln { x } \right) } \right\} \\ \\ \frac { dy }{ dx } ={ \left( \ln { x } \right) }^{ x }\left\{ \frac { 1 }{ \ln { x } } +\ln { \left( \ln { x } \right) } \right\}$